2014
DOI: 10.1039/c3cp54429j
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polydimethylsiloxane on transparent and hydrophobic waterborne polyurethane coatings containing polydimethylsiloxane

Abstract: The effects of polydimethylsiloxane (PDMS) on phase separation, optical transmittance and surface properties including surface composition, morphology and wettability of waterborne polyurethane (WPU) containing PDMS were investigated. After the introduction of PDMS into the WPU backbone by polymerization, the large difference in the solubility parameter of the non-polar PDMS segment and the high-polar urethane segments promoted PDMS enrichment at the air-polymer interface and enhanced phase separation, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 43 publications
3
45
1
Order By: Relevance
“…It is observed that WPU films are formed by particles ranging from 30 nm to 50 nm after deformation and interdiffusion, which is consistent with the result of particle size distribution. Migration of polyether functional PDMS do not have regular effect on the surface topography of WPU films in height maps, which is in good agreement with the analysis of SEM, but is not in accordance with literature data [14]. This is due to low degree of bulk phase separation in all four samples suggested by FTIR and EDS results, which exerts a strong influence on the surface topography [25].…”
Section: Sem-eds and Afm Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…It is observed that WPU films are formed by particles ranging from 30 nm to 50 nm after deformation and interdiffusion, which is consistent with the result of particle size distribution. Migration of polyether functional PDMS do not have regular effect on the surface topography of WPU films in height maps, which is in good agreement with the analysis of SEM, but is not in accordance with literature data [14]. This is due to low degree of bulk phase separation in all four samples suggested by FTIR and EDS results, which exerts a strong influence on the surface topography [25].…”
Section: Sem-eds and Afm Analysissupporting
confidence: 87%
“…At present, the application of polysiloxanes modification is mainly concentrated on solvent-borne polyurethane, with little research on its application in WPU. In the study conducted by Wu et al, WPU coatings modified with PDMS possess high hydrophobic property and optical transmittance [14]. Naghash et al incorporated allyl 3-(triethoxysilyl) propyl carbamate (ATESPC) into WPU using emulsion copolymerization and examined its effect on the emulsion and thermal performance of the films [15].…”
Section: Introductionmentioning
confidence: 99%
“…The peaks appearing in the range of 2856-2925 cm −1 correspond to the stretching vibration of the alkyl chain in the castor oil. The C O group from urethane of the polyurethane moiety generates two peaks that corresponds to the hydrogen bonded C O group at 1714 cm −1 and the free C O group at 1743 cm −1 [27]; the ester C O group of castor oil may be involved in the peak at 1743 cm −1 . For the SiWPU films, the peak at around 807 cm −1 is attributed to the absorption of Si-CH 2 bond [27], which cannot be found in the WPU spectrum.…”
Section: Atr-ftir Of the Siwpu Hybrid Filmsmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) has unique properties such as low surface energy, hydrophobicity, high flexibility, transparency and excellent thermal, oxidative and UV stability. It has been shown that the adequate inclusion of PDMS prepolymers, such as hydroxyl-hexyl, aminopropyl, methyl aminopropyl PDMS into a WPU matrix can improve the water resistance and hydrophobic surface properties of WPU films [7][8][9][10][11]. However, their mechanical properties are not improved much and even decreased with high PDMS content due to the extremely high incompatibility between the urethane (or urea) and the PDMS segments.…”
Section: Introductionmentioning
confidence: 99%